Warung Bakmi Mbah Gito: Eksplorasi Pengalaman terkait Produk dan Ruang di Wisata Kuliner Berbasis Budaya Jawa - Hanggraito, Ahmadintya Anggit; Budiani, Budiani (Journal of Indonesian Tourism, Hospitality and Recreation, 2022)
ABSTRACTThe existence of Warung Bakmi Mbah Gito as a culinary tourism shows the importance of studying culinary products and space attributes that promote local culture. This study tries to explore the experience of Javanese culture-based culinary products and spaces at Warung Bakmi Mbah Gito. data collection methods through observation, in-depth interviews, and questionnaires. The results of descriptive statistics were triangulated with qualitative data in order to produce conclusions. The results of this study indicate that the experience of culinary products at Warung Bakmi Mbah Gito is focused on tangible and intangible products. The products are related to local food using original and natural ingredients that come from the village. Meanwhile, the intangible product is related to the space atmosphere and service model. In addition, the main variables in the space experience at Warung Bakmi Mbah Gito are focused on the design of the room and the music. This study is expected to provide another understanding in the development of culinary tourism destinations based on local culture. Especially in other areas that have food with a different local cultural base.ABSTRAKEksistensi Warung Bakmi Mbah Gito sebagai sebuah wisata kuliner menunjukkan pentingnya kajian terhadap produk kuliner dan atribut ruang yang mengangkat budaya lokal. Penelitian ini berusaha mengeksplorasi pengalaman produk dan ruang kuliner berbasis budaya jawa di Warung Bakmi Mbah Gito. metode pengumpulan data melalui observasi, wawancara mendalam, dan kuesioner. Hasil statistik deskriptif ditriangulasi dengan data kualitatif agar menghasilkan kesimpulan. Hasil dari penelitian ini menunjukkan pengalaman produk kuliner di Warung Bakmi Mbah Gito tertuju pada produk tangible dan intangible. Produk tangible terkait dengan makanan lokal yang menggunakan bahan asli dan alami yang berasal dari desa. Sedangkan, produk intangible terkait dengan atmosfer ruang dan model pelayanan. Selain itu, variabel utama dalam pengalaman ruang di Warung Bakmi Mbah Gito tertuju pada desain ruang dan musik yang dimainkan. Penelitian ini diharapkan akan memberikan pemahaman  lain dalam sebuah pengembangan destinasi wisata kuliner berbasis budaya lokal. Terutama di daerah lain yang memiliki makanan dengan basis budaya lokal yang berbeda.